Pengaruh Model Pembelajaran Reciprocal Teaching Berbasis Literasi Digital Terhadap Hasil Belajar Bahasa Indonesia Siswa Sekolah Dasar - Maskura, St Ainil; Irviana, Ira (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2023)
The digital literacy-based Reciprocal Teaching learning model is a learning model consisting of the process of teaching material to its peers. This learning model d a pat merangs a ng pupil untuk belaj a r m a ndiri, creatiive and more active dalamcarry out proses teaching and learning. The Digital Literacy-based Reciprocal Teaching model establishes four st a rtegi pemahaman Mandiri, namely summarizing the material, making questions and solving them. The research design used is a pretesst-possttest control group design, designed this combination of experiments or combined controls selected according to random. This research was conducted at SD Negeri Parang Tambung 1 Makassar City which is located at Jalan Daeng Tata No.80 Parang Tambung, Tamalate District, Makassar City, South Sulawesi Province. This research was conducted during the odd semester of the 2020/2021 academic year. The initial research variable is the whole thing that is of any form that is determined by the author to be studied so that information about it is obtained. The variables in this study are free variables and bound variables. The free variable in this study is the Digital Literacy-based Reciprocal Teaching model which is referred to as X. Bound variables in this study are the learning outcomes of students in lessons Indonesian SDN Parang Tambung 1 which is referred to as Y. The population in this study is the total class VI students of SDN Parang Tambung 1 Makassar City which consists of 2 classes totalling 40 students. In this study, the sample taken was 36 students with a population of 40 students based on Isaac and Michael's table for a signification level of 0.05, so the sample obtained had a 38% confidence level in the population. Data collection techniques are carried out by observation, documentation, and tests. Based on the results of the research that has been described, it can be seen that the digital literacy-based Reciprocal Teaching learning model on Indonesian learning outcomes at SD Makassar City has an effect. It is based on the results of the hypothesis formulation obtained 0.04 so that the sig value. (2 tailed) < 0.05, it is known that there is a significant influence between the learning outcomes of the experimental group and the control group.